School Attendance, Child Labour, and Remittances from International Migration in El Salvador - Acosta, Pablo (2012)
International migrant remittances can increase household budget and reduce liquidity constraint problems, generating consumption and investment opportunities for recipient households. In particular, remittances can enable investing in children's human capital and reduce child labour, key outcomes from the perspective of growth in a developing country. Using data for El Salvador, this article shows: a) a null or insignificant overall impact of remittances on schooling; b) a strong reduction of child wage labour in remittance-recipient households; and c) an increase in unpaid family work activities for children in those households. Moreover, the evidence shows important differences by gender and age of the child in consideration. While girls seem to indeed increase school attendance upon remittance receipts by reducing labour activities, boys do not benefit on average from higher schooling but some time substitution takes place favouring family work activities over paid jobs. And among secondary school-aged children, the impact of remittance may even be negative for educational prospects. These results suggest the presence of differences in the allocation of resources within the household.